Biocontrol potential of Aspergillus terreus, endophytic fungus against Rigidoporus microporus and Corynespora cassiicola, pathogens of rubber tree. (2nd October 2021) - Mahendran, Thamby Rajah; Thottathil, Gincy P.; Surendran, Arthy; Nagao, Hideyuki; Sudesh, Kumar
Abstract: The pathogenic fungi, Rigidoporus microporus and Corynespora cassiicola are among the major agents of root and leaf disease of rubber tree ( Hevea brasiliensis ). In this study, endophytic fungi were isolated from seeds of H. brasiliensis obtained from different regions of Malaysia to determine the diversity of endophytes inhabiting the seeds and to select a potential biocontrol agent against selected Hevea pathogens. Through morphological observation and molecular identification, six genera were identified namely Aspergillus, Colletotrichum, Diaporthe, Lasiodiplodia, Mucor and Pseudofusicoccum . Isolate PN3 which showed 99.82% identity to Aspergillus terreus was selected as a candidate to evaluate its biocontrol potential against R. microporus and C. cassiicola as it displayed promising inhibitory potential in preliminary experiments. A. terreus showed inhibition of 81.24%, 70.35% and 64.19% against R. microporus and two races of C. cassiicola namely CLN 16 and CSB 16 respectively in dual culture assay. In dipped stick inhibition assay, A. terreus showed 100% inhibition to the growth of R. microporus. A. terreus also reduced infection of leaves cultured with C. cassiicola CLN 16 and CSB 16 by 93.33% and 86.67% respectively. This study has identified some of the fungal species inhabiting the seeds of H. brasiliensis which may have potential as biocontrol agents.